Globalization in higher education: the evolution and trend. - Đào, Thị Bích Thủy (International school. Vietnam national university, Hanoi, 2020)
Higher education is said to be an essential foundation for personal, social and economic success in a globalized economy. The 21st century is the age of globalization. With dynamic processes of increasing interdependence, growing competition, communication technologies and changing skill requirements in the labor market, globalization has its impact on the life of higher education. The paper provides an overall view on the evolution of and the trend in the globalization of higher education. The first wave of higher education globalization mostly meant the movements of students across borders when students in one country moving overseas for their university education. Over the past decades, the number of international students enrolled outside their country of citizenship has risen dramatically, from 0.8 million worldwide in 1975 to double at 1.7 million in 1995 and double again at 3.7 million in 2009 and this number is forecasted to reach about 5.8 million by 2020. There is a clear tendency of international student movement from developing to developed countries. Asia formed the largest group of sending students to overseas study, account for more than 50% of the world mobile students and North America and Western Europe is the predominant destination that receives international students, account for nearly 60% of the world mobile students. The new wave of higher education globalization includes the movements of teachers, programs and institutions across borders and has grown rapidly over the last decade. This form enables students to take degree offered by a foreign university without leaving their home country. International mobility in programs and institutions poses many opportunities and challenges to institutions in developing countries as it creates both collaboration and competition between foreign and domestic institutions. In one hand, international mobility of programs opens up many opportunities for collaboration and development for higher education institutions in foreign developed and domestic developing countries. The various forms of program mobility present the variety of models for collaboration between foreign and domestic institutions and bring ample benefits to both sides. In the other hand, international institution mobility increases competition among foreign and domestic institutions since physical presence of foreign providers forces domestic providers to have more incentive for innovation and improvement of their quality in courses, management and governance. The ever-growing demand for higher education in developing countries plus the speed up of globalization in higher education opens a perspective for collaboration and development between foreign and domestic institutions that help to build the countries’ domestic capacity to provide good quality higher education.